Habits and Preferences in Sunscreen Usage Among Healthcare Professionals in the UK - Petrou IA; Tan SP; Birnie AJ (Dove Medical Press, 2023)
Ilia Anna Petrou,1 Siao Pei Tan,2 Andrew J Birnie2 1Dermatology Department, University College London Hospitals NHS Foundation Trust, London, UK; 2Dermatology Department, East Kent Hospitals University NHS Foundation Trust, Canterbury, Kent, UKCorrespondence: Ilia Anna Petrou, Friends Dermatology Centre, Kent & Canterbury Hospital, 1937 Building- Main Floor, Ethelbert Road, Canterbury, Kent, CT1 3NG, UK, Email ilia.petrou@nhs.netAbstract: Raising awareness about sun protection is an ongoing challenge. In 2018, a Survey Monkey questionnaire was distributed among healthcare professionals in the United Kingdom looking at their own habits of sunscreen usage. A total of 165 responses were collected. Eighty-nine percent of our respondents would use sunscreen when outdoors 11am- 3pm on a cloudless, sunny day in August in the UK. However, only 27% of these healthcare professionals would regularly reapply sunscreen every 2 hours. The most important reason for using sunscreen was avoiding sunburn (importance weighted average of 4.71, on a scale from 1 to 5), followed by avoiding skin cancer (4.49) and skin ageing (4.06). On an importance scale from 1 to 5, the most important sunscreen characteristics, when choosing or recommending a product, were the level of UVA protection (importance weighted average 4.48), its stickiness (3.85) and degree of water-resistance (3.77).Keywords: photodermatology, ultraviolet radiation, cancer